Water Scarcity and Degradation in the Rio San Juan Watershed of Northeastern Mexico - Návar Cháidez, José de Jesús (Frontera Norte, 2017)
Freshwater has become a limited resource for development in the Rio San Juan watershed, the major tributary of the Lower Rio Bravo, in northeastern Mexico. The results of unsustainable practices include: the inter-basin transfer of freshwater, groundwater depletion, low or nonexistent river flows in several river segments, rising pollution levels, high per capita water use, low irrigation efficiency, the disturbance of riparian ecosystems, and social conflict between water uses and users, all exacerbated by recurrent drought episodes of several temporal scales. This report shows that improving sustainable management practices could make it possible to meet current conventional water demands for agriculture, population, industry, as well as for riparian environments and ease social tension but policies are required to increase water use efficiency in all economic sectors, together with new partnerships that cut across disciplinary and professional boundaries. Escasez de agua y degradación en la cuenca del río San Juan del noreste de México Resumen El agua se ha convertido en un recurso limitante para el desarrollo en la cuenca del río San Juan, el mayor tributario del bajo Río Bravo, del noreste de México. Señales de manejo no sostenible incluyen: la transferencia del agua entre cuencas, la disminución del nivel del agua de los acuíferos, la presencia de caudales mínimos e inexistentes en varios segmentos de los ríos, aumento en los niveles de contaminación, altos consumos per cápita, baja eficiencia en la agricultura, el disturbio de los ecosistemas acuáticos y los problemas sociales entre usos e usuarios, todos estos magnificados por la presencia de sequías recurrentes de diferentes escalas temporales. En este reporte se muestra que el reforzamiento de las prácticas de manejo sostenible del agua podrían cumplir con las demandas para la agricultura, la población, la industria y el medio ambiente además de aliviar la inestabilidad social pero se requiere de políticas para aumentar la eficiencia en el uso en todos los sectores de la economía además de nuevas formas de integración que crucen las fronteras interdisciplinarias y profesionales.